Enriched of Orange Jam (Marmalade) with vitamin C - Jebreen, Ali; Aznam, Nurul ‘Izzah Binti Khairul (Journal of Agri-Food Science and Technology, 2024)
This study explores the enrichment of orange jam, also known as marmalade, with vitamin C. Orange jam is a popular preserve enjoyed worldwide, prized for its tangy flavor and versatility. However, the conventional processing methods involved in its production may lead to a loss of essential nutrients, including vitamin C. To address this issue, the enrichment of orange jam with vitamin C is proposed to enhance its nutritional value. Various techniques can be employed to enrich orange jam with vitamin C, including fortification during the manufacturing process or through the addition of vitamin C-rich ingredients such as citrus fruits or supplements. Additionally, the stability of vitamin C in jam formulations must be considered to ensure its efficacy throughout the product's shelf life. The enrichment of orange jam with vitamin C offers numerous benefits, including enhancing its nutritional profile, boosting consumer health, and potentially extending its market appeal. Furthermore, the addition of vitamin C may contribute to the preservation of the jam by acting as an antioxidant, thereby extending its shelf life. In conclusion, enriching orange jam with vitamin C presents a promising opportunity to enhance its nutritional value and appeal to health-conscious consumers. Further research is warranted to optimize enrichment techniques, ensure stability, and evaluate the sensory attributes of fortified orange jam to meet consumer expectations and preferences. This research is contributes to explore the benefit of vitamin c addition on orange jam.